Novel neutralizing chicken IgY antibodies targeting 17 potent conserved peptides identified by SARS-CoV-2 proteome microarray, and future prospects - Li, Jin; Liang, Te; Hei, Ailian; Wang, Xiangbin; Li, Huijun; Yu, Xiaobo; Zhao, Rui; Gao, Peng; Fang, Cong; Zhou, Ji; Li, Maogang; He, Ellen; et al. (Frontiers in Immunology, 2022)
An approach toward novel neutralizing IgY polyclonal antibodies (N-IgY-pAb) against SARS-Cov-2 S-ECD was developed. The novel N-IgY-pAb and its intranasal spray response against the wild type (“'WH-Human 1”) SARS-Cov-2 virus, variants of Delta and Omicron was up to 98%. Unique virus peptides binding to N-IgY-pAb were screened by a SARS-Cov-2 proteome microarray. Seventeen mutation-free peptides with a Z-score > 3.0 were identified as potent targets from a total of 966 peptides. The new findings show that one is in the RBM domain (461LKPFERDISTEIYQA475), two are in the NTD domain (21RTQLPPAYTNSFTRG35, 291CALDPLSETKCTLKS305), four are in the C1/2-terminal (561PFQQFGRDIADTTDA575, 571DTTDAVRDPQTLEIL585, 581TLEILDITPCSFGGV595, 661ECDIPIGAGICASYQ675), three are in the S1/S2 border (741YICGDSTECSNLLLQ755, 811KPSKRSFIEDLLFNK825, 821LLFNKVTLADAGFIK835), one target is in HR2 (1161SPDVDLGDISGINAS1175) and one is in HR2-TM (1201QELGKYEQYIKWPWY1215). Moreover, five potential peptides were in the NSP domain: nsp3-55 (1361SNEKQEILGTVSWNL1375), nsp14-50 (6144HHANEYRLYLDAYNM6425), ORF10-3 (21MNSRNYIAQVDVVNFNLT38), ORF7a-1 (1MKIILFLALITLATC15) and ORF7a-12 (111TLCFTLKRKTE121). We concluded that the N-IgY-pAb effectively neutralizing the SARS-CoV-2. The new findings of seventeen potent conserved peptides are extremely important for development of new vaccines and “cocktails” of neutralizing Abs for efficient treatment of patients infected with SARS-CoV-2.